101 essays that will change the way you think - Wiest, Brianna (2017)
"Over the past few years, Brianna Wiest has gained renown for her deeply moving, philosophical writing. This new compilation of her published work features pieces on why you should pursue purpose over passion, embrace negative thinking, see the wisdom in daily routine, and become aware of the cognitive biases that are creating the way you see your life. Some of these pieces have never been seen; others have been read by millions of people around the world. Regardless, each will leave you thinking: This idea changed my life."--provided by publisher.
Includes bibliographical references and Internet addresses.
Keywords: Self-actualization (Psychology); Change (Psychology); Thought and thinking; Philosophy; Thinking; Philosophy; Changement (Psychologie); Pensée.; Philosophie; thinking; philosophy; Change (Psychology); Philosophy; Self-actualization (Psychology); Thought and thinking; Self-help publications; Essays; Self-help publications; Essays